Gender difference in the conative component of entrepreneurial orientation - Andrej Bertoncelj; Darko Kovaéc (Journal for East European Management Studies, 2009)
The aim of this paper is to investigate the question of gender difference in the entrepreneurial orientation of managers in the post-transition economy of Slovenia. The concept of intervening variables as parts of the conative components of entrepreneurial orientation is introduced and gender differences are examined between variables. 183 Slovene top and middle managers were analysed in this respect. The results indicate that there are no gender differences in the variable to spot opportunities, to risk, to innovate, and in the intervening variable to plan, and to follow procedures, but a gender difference exists in the intervening variable to analyse, to quantify, and to justify and in the intervening variables of dexterity and craftsmanship, which could be attributed to gender occupational concentration. – – Der Zweck dieses Beitrags ist es, die Frage der geschlechterspezifischen Unterschiede zwischen Managern in Bezug auf ihre unternehmerische Orientierung im Kontext der Transformationsituation in Slowenien zu untersuchen. Dazu wird das Konzept der intervenierenden Variablen als Teile der konativen Komponenten unternehmerischer Orientierung eingeführt und die Geschlechterunterschiede anhand von Variablen untersucht. 183 obere und mitllere Manager wurden dazu befragt. Die Ergebnisse zeigen, dass es keine Geschlechterunterschiede gibt bezüglich der Nutzung von Möglichkeiten, dem Risiko- und dem Innovationsverhalten und in Bezug auf die Planung und Befolgung von Verfahren. Allerdings bestehen geschlechterspezifische Unterschiede bei den intervenierenden Variablen zu analysieren, zu quantifizieren and zu beurteilen sowie bei der Geschicklichkeit und dem handwerklichen Könnens, die in einer berufsbedingten Konzentration der Geschlechter begründet liegen könnten.
Keywords: 650; Entrepreneurial orientation; gender difference; middle managers; conation; Slovenia